Avaliação do uso de fibra obtida por eletrofiação contendo óleo ozonizado na cicatrização de lesões causadas por Leishmania Amazonensis em modelo animal - Tres, Daniela Patrícia (2024)
Cutaneous leishmaniasis (CL) is a neglected disease, with cases increasing annually, with CL lesions generating severe scars, causing psychosocial shocks to sufferers. The treatments currently available are high cost, nephrotoxic, hepatotoxic and with reports of resistance, in addition, patients sometimes do not adhere to them due to side effects and dosage. Ozonated sunflower oil has been used to treat wounds. Electrospinning allows the development of nanofibers incorporated with various compounds, which stand out for their low cost and cellular activity. OBJECTIVE: Therefore, the objective of this work was to test ozonized sunflower oil incorporated into electrospun fibers, to be used in conjunction with the reference treatment (meglumine antimoniate), in skin lesions caused by Leishmania amazonensis, in an animal model. METHODOLOGY: Experimental study, where 4 groups of female Balb/C mice were infected with L. amazonensis, the first group was treated only with meglumine antimoniate, the second was treated with meglumine antimoniate and ozonized sunflower oil incorporated into the fiber electrospun, the third was treated with meglumine antimoniate and sunflower oil incorporated into the electrospun fiber and the fourth group was not treated. RESULTS: The ozone concentration in the oil and fiber remained stable. There was no statistical difference in relation to nitric oxide production, animal weight loss, IL-6 and TNF-α secretion, lesion thickness and leukocyte count in the groups studied. Macroscopically, group 1 showed practically complete healing of the lesion. Regarding the parasitic load present in the lesion on the animal's paw, its presence was observed after 30 days, only in group 2. Regarding the evaluation of the leishmanicidal activity of the ozonized oil on amastigote forms in vitro, there was a statistical difference only in the groups treated with meglumine antimoniate and ozonized oil concentrations of 300 µg/ml and 150 µg/ml. Histologically, meglumine antimoniate showed greater thickness of the epidermis, being significant compared to other groups, and presented the smallest leukocyte infiltrate. CONCLUSION: New studies are needed to improve the beneficial concentration of ozone in oil, as there are still many gaps and controversies in the literature on the subject, so it will be possible to carry out studies with promising results in vivo.